Permaculture design of the recreation area in the neighborhood Park Alexandrina at city of Presidente Prudente/SP: Initial proposal - Agostinho, Annelise Picolo; Zanchetta, Gabriela; Okimoto, Fernando Sérgio (Technical and Scientific Journal Green Cities, 2021)
.